Grundtvig og den middelalderlige kontemplative tradition - Pedersen, Kim Arne (Grundtvig-Studier, 1993)
Grundtvig and the medieval 'kontemplative' tradition Jørgen Pedersen: Prior omnium sapientia. Reviewed by Kim Arne Pedersen